Evaluation of lateral force distribution of frame and shear wall considering soil-structure interaction and foundation flexibility - Iman Hakamian (مهندسی و مدیریت ساخت, 2024)
This study investigates the effect of foundation flexibility on the lateral force distribution of moment frames and shear walls. This distribution has been represented in terms of shear-moment ratio that are developed in columns, and normalized by the fix base shear and total first story moments, respectively. Four nonlinear moment resisting frames, in different heights including 5-story, 10-story, 15-story and 20-story, with nonlinear shear wall are considered, and nonlinear static analysis are performed in the fixed and flexible bases by Opensees. BNWF approach has been employed to account foundation flexibility due to soil structure interaction. Footings are modeled as beam column elements, and soil foundation interface is modeled by closely spaced, independent nonlinear spring elements. Based on the obtained results in this study, for all the investigated frames the normalized shears and moments in the first story in flexible condition are higher than the fixed base, meaning that the greatest effect due to foundation flexibility is related to forces corresponding to the first story. Foundation flexibility reduces the shear wall's stiffness and therefore, lower forces are carried out by the wall. As a result, the extra forces are developed in frames elements.